La Enseñanza de las Ciencias Naturales desde el enfoque de la Apropiación Social de la Ciencia, la Tecnología y la Innovación ASCTI en la educación básica–media - Lopez-Rivera, Zoila Carolina (Revista Científica, 2015)
This paper presents some considerations regarding different tensions and issues between current Natural Sciences teaching and the emerging demands from the perspective of Social Appropriation of Science, Technology, and Innovation (SASTI). It also presents theoretical and conceptual aspects resulting from this approach. Finally, it offers a methodological reflection based on Social Educational Innovation (ISE) which allows the characterization of the basic elements that would base Natural Sciences teaching from ASCTI.